Evaluation of anxiety and depression and its associated factors using HADS questionnaire in nasolacrimal duct obstruction patients - Al-Abbas, Ali Hadi Saud (2022)
Introduction: Nasolacrimal duct obstruction (NLDO) also known as dacryostenosis, is an anatomic obstruction that may occur along the lacrimal drainage pathway and may be congenital or acquired. Acquired NLDO may be primary acquired NLDO (PANLDO) or secondary acquired NLDO with the primary appearing as the most common type. Most NLDO patients complain of occassional conjunctival hyperemia and epiphora. Psychological sequelae of NLDO is often not addressed by the treating physician. Thus, identification of such sequelae may be helpful to these patients and brings attention to the need of referral to the appropriate channels for further evaluation. Objective: The aim of our study was to evaluate the levels of anxiety and depression in NLDO patients and to determine the potential predictors associated with it. Methods: A cross-sectional study was conducted between March 2021 and March 2022 involving NLDO patients attending eye clinics in Hospital Universiti Sains Malaysia. Patients were given the validated Hospital Anxiety and Depression Scale (HADS) and an evaluation of Munk score. After completion, the questionnaires were calculated and scored, and statistical analysis was done using Statistical Package for the Social Science (SPSS Inc. Version 26). Results: A total of 109 patients diagnosed with NLDO participated in this study. The demographic and clinical variables assessed were age, gender, race, marital status, highest education, duration of NLDO in years and severity of epiphora. The mean HADS-Depression score was 4.61 (SD 3.4) with a range of scores from (0 to 12). There were 25.7% (n=28) of the total number of patients had depression. Seventy-four and three tenths percent of the patients had normal depression scores, while 22.0% and 3.7% of the participants had mild and moderate depression respectively. The mean HADS-Anxiety score was 5.98 (SD 4.34) with a range of scores from (0-14). A total of 35.8% (n=39) of patients had anxiety. Sixty-four and two tenths percent of the patients are normal, while 19.3% and 16.5% of the patients had mild anxiety and moderate levels of anxiety respectively. A score of more than 8 represents mild depression or anxiety. There were significant associations between age, NLDO duration, epiphora and dabbing with depression levels based on the multiple linear regression (p<0.05 for all variables tested). Similarly, there were significant associations between epiphora and dabbing 2-4/day and 5-10/day with increased anxiety levels among the patients where p<0.05 for the variables. In addition, depression scores decreased by 0.048 with age among the patients. Similarly, NLDO duration of 1-5 years and >5 years have 4.054 and 4.683 chances of having depression when compared to single patients respectively. For anxiety, for patients with NLDO duration of > 5years have 2.642 chance of experiencing the condition that those with the duration of < 5 years. Conclusion: This study showed a low prevalence of depression and anxiety among NLDO patients. Younger age group, NLDO duration and epiphora requiring dabbing were associated with depression among the patients; Whereas NLDO duration and epiphora requiring dabbing were associated with increased level of anxiety.